Optimal design of infinite impulse response digital filter banks - Chen, Yue (2014)
In this report, the author elaborates the sequential weighted infinite impulse reponse (IIR) filter banks (FB). This method converts the original WLS design problem into a sequence of WLS sub-problems. In eac of the WLS sub-problem, only one secord-order factor (SOF) of the denominator and numerator is updated and iteratively solved by a constrained WLS algorithm.